Performance analysis of commercial audio video streaming product using metamaterial antenna. Issue 9 (September 2017) - Nazarruddin, Nazatul Shuhada Bt Ahmad; Islam, Mohammad Tariqul; Alam, Touhidul
Abstract: This article discusses about the Wi‐Fi performance of a designated metamaterial unit cell inspired antenna in a commercial audio and video (A/V) streaming product. The designated antenna was integrated into the A/V streaming product called device under test (DUT) by connecting UFL‐SMA cable to the WLAN module RF circuit. The performance of the antenna is measured taking WLAN throughput data after considering the internal noise condition in the DUT. The WLAN throughput data are measured by using a commonly used network testing tool called Iperf. Iperf can function as a client or server. By creating transmission control protocol and user datagram protocol data streams, personal computer act as a server, transmitting packets to the DUT which acts as a client, so that the network throughput can be measured between two ends. This measurement is done in a shielded room to eliminate other environment noise effect. Besides of analyzing the internal noise, the environmental noise effect has also been conducted. As an overall, a feasibility analysis on the antenna performance in term of DUT internal noise, WLAN throughput and environmental effect on the throughput performance will be presented in this article.